Moral disagreements : classic and contemporary readings - Gowans, Christopher W. (Routledge, 2000)
Can moral disagreements be rationally resolved? Can universal human rights be defended in face of moral disagreements? The problem of moral disagreement is one of the central problems in moral thinking. It also provides a stimulating stepping-stone to some of the perennial problems of philosophy, such as relativism, scepticism, and objectivity. Moral Disagreements is the first anthology to bring together classic and contemporary readings on this key topic. Clearly divided into five parts; The Historical Debate; Voices from Anthropology; Challenges to Moral Objectivity; Defenses of Moral Obje.